2014
DOI: 10.1002/adma.201305593
|View full text |Cite
|
Sign up to set email alerts
|

High Capacity, Easy Release Adhesives From Renewable Materials

Abstract: Reversible adhesives composed of renewable materials are presented which achieve high force capacities (810 N) while maintaining easy release (∼ 0.25 N) and reusability. These simple, non-tacky adhesives consist of natural rubber impregnated into stiff natural fiber fabrics, including cotton, hemp, and jute. This versatile approach enables a clear method for designs of environmentally-responsible, reversible adhesives for a wide variety of applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 34 publications
1
50
0
Order By: Relevance
“…A prominent approach in this area is to create angled microstructures including angled pillars, [83,117,[129][130][131][132][133][134][135][136][137] angled "flap" features, [83,[138][139][140][141][142][143][144] and hierarchical structures. [40,42,152,153] Additionally, directional geometric or material features can be incorporated into film adhesives. This approach is effective with switching ratios typically ranging from 10 to 60.…”
Section: Controlled Loadingmentioning
confidence: 99%
“…A prominent approach in this area is to create angled microstructures including angled pillars, [83,117,[129][130][131][132][133][134][135][136][137] angled "flap" features, [83,[138][139][140][141][142][143][144] and hierarchical structures. [40,42,152,153] Additionally, directional geometric or material features can be incorporated into film adhesives. This approach is effective with switching ratios typically ranging from 10 to 60.…”
Section: Controlled Loadingmentioning
confidence: 99%
“…The utilization of traditional adhesive materials are mostly composed of synthetic components, which are generally thrown away after the use, and it may not able to support a high load since it was difficult to remove while maintaining reversibility (Bartlett and Crosby, 2014). A renewable and reusable adhesive exhibited high force capacity and easy release characteristics was investigated in 2013.…”
Section: Properties Of Adhesivesmentioning
confidence: 99%
“…A renewable and reusable adhesive exhibited high force capacity and easy release characteristics was investigated in 2013. In that research, force capacity as high as 810 N over 100 cm 2 contact areas was examined and the results showed that it can enable high performing and reuse over many loading cycles (Bartlett and Crosby, 2014).…”
Section: Properties Of Adhesivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many wall-climbing robots have used electrostatics to adhere to insulating substrates [19][20][21][22][23][24], using low power but typically requiring voltages too high for standard electronic components. Some of the adhesion in these systems is due to the inherent adhesion of the tacky polymers used as insulators, which causes the electrodes to remain adhered even once the voltage is removed [25,26]. This makes them less desirable for clutching, where an automatic release would be advantageous.…”
Section: Introductionmentioning
confidence: 99%